2022
DOI: 10.3389/fpubh.2022.952269
|View full text |Cite
|
Sign up to set email alerts
|

Burnout, negative emotions, and wellbeing among social workers in China after community lockdowns during the COVID-19 pandemic: Mediating roles of trait mindfulness

Abstract: ObjectiveThis study aimed to investigate burnout situation of social workers (SWs) who experienced the COVID-19 pandemic-related community lockdown 1 year before, and to assess the protective value of trait mindfulness (TM) in states of burnout.MethodWe surveyed the burnout, trait mindfulness, negative emotions (NEs) and wellbeing (WB) of 182 social workers provided services to Wuhan lockdowns community by COVID-19 one year before. Burnout were measured using the Maslach Burnout Inventory–Human Services Survey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…In the present study, the Chinese version of Maslach's Burnout Inventory-Human Services Survey (MBI-HSS) ( 67 ) with 17 items was used to assess the extent of job burnout of healthcare workers, revised by Zhang ( 68 ). This version of MBI-HSS-17 has been proved to have good reliability and validity when revised ( 68 ), and has been widely used in previous studies ( 69 , 70 ). It comprised a total of 17 items that measure job burnout on a seven-point Likert scale, containing three dimensions: emotional exhaustion (EE, seven items), depersonalization (DA, three items), and personal accomplishment (PA, seven items).…”
Section: Methodsmentioning
confidence: 99%
“…In the present study, the Chinese version of Maslach's Burnout Inventory-Human Services Survey (MBI-HSS) ( 67 ) with 17 items was used to assess the extent of job burnout of healthcare workers, revised by Zhang ( 68 ). This version of MBI-HSS-17 has been proved to have good reliability and validity when revised ( 68 ), and has been widely used in previous studies ( 69 , 70 ). It comprised a total of 17 items that measure job burnout on a seven-point Likert scale, containing three dimensions: emotional exhaustion (EE, seven items), depersonalization (DA, three items), and personal accomplishment (PA, seven items).…”
Section: Methodsmentioning
confidence: 99%
“…During the COVID-19 pandemic, the Chinese government implemented a series of measures at the community level to curb the spread of the virus (11). These measures include community lockdowns with different degrees, strict restrictions on entering and leaving communities and resident outdoor activities (12), and grid-based and carpet-style management (13). Community residents actively participated in epidemic prevention and control and transformed individual involvement into collective efficacy to address disaster events faced by communities collectively (14).…”
Section: Introductionmentioning
confidence: 99%
“…COVID-19 is a global health threat (5). Studies have shown that COVID-19 has had a negative effect on the mental health of different groups of people (6)(7)(8)(9). A large number of individuals have been forced to rapidly transition to a new way of life because of COVID-19 (10).…”
Section: Introductionmentioning
confidence: 99%